2008
DOI: 10.1197/jamia.m2558
|View full text |Cite
|
Sign up to set email alerts
|

A Heuristic Indication and Warning Staging Model for Detection and Assessment of Biological Events

Abstract: Used as a complement to current epidemiological surveillance methods, our approach could aid global public health officials and national political leaders in responding to biological threats of international public health significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…[6-9] Argus collects, in an automated process, several thousand local, native-language Internet media articles daily. [10] Bayesian software tools and Boolean search strings, based on a taxonomy of infectious disease, identify candidate relevant articles.…”
Section: Methodsmentioning
confidence: 99%
“…[6-9] Argus collects, in an automated process, several thousand local, native-language Internet media articles daily. [10] Bayesian software tools and Boolean search strings, based on a taxonomy of infectious disease, identify candidate relevant articles.…”
Section: Methodsmentioning
confidence: 99%
“…Project Argus is another Internet-based biosurveillance project hosted at the Georgetown University Medical Center. A retrospective study of the SARS outbreak by Georgetown researchers showed that subtle indications (unseasonal bad influenza) were reported in online news sources as early as September 2002 [10]. Despite the great potential in mining early indications of disease outbreaks from online sources, identification of relevant online articles is challenging in practice due to the vast amount of ever growing publications on the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Open-source media analysis may detect evidence of biological threats and/or social disruption, leading to direct and indirect indicators of outbreaks. 16 Moreover, this analysis may provide warning of outbreaks sooner than traditional surveillance methods. 17 Sophisticated analytic techniques have been applied to existing data sources to better distinguish anomalies from baseline data.…”
Section: Event-based Biosurveillancementioning
confidence: 99%
“…Direct indicators and warnings are unambiguous information that an event is indeed occurring. 16 Indirect indicators and warnings are proxy data that indicate the circumstances wherein a biosurveillance event is likely to occur.…”
Section: Input Data Attribute Familymentioning
confidence: 99%